Simulation of Shock-to-Detonation Transition by OpenFOAM - Thien Xuan Dinh; Masatake Yoshida; Shuichi Ishikura (Aerospace)
Shock-to-detonation transition (SDT) is the detonation of explosive charge triggered by the shock pressure from a nearby detonated explosive or an impact at high speed. A good prediction of SDT is a key in the design of explosives’ use, storage, and transportation. Typically, SDT simulation must use designated commercial software; therefore, a high license cost is necessary. This paper presents a simulation of SDT by a cost-effective hydrodynamic code developed on an open-source code framework, OpenFOAM. The code adopted the multi-material Eulerian method, Ignition and Growth reaction rate model, and Riemann solver to solve the shock-induced detonation phenomenon. The code was verified by a Pop plot calculation and a sympathetic detonation simulation. In the Pop plot calculation, the distance-of-run to the detonation of Composition B depending on the initial shock pressure was simulated. The reactant and product phases of Composition B were modeled by the Jone–Wilkins–Lee (JWL) equation of state (EOS). The aluminum plate used to create the initial shock pressure was modeled by shock Mie–Gruneisen (MG) EOS. The predicted distance-of-run against the initial shock pressure was in good agreement with an empirical correlation and experimental data. In the sympathetic detonation simulation, the charge explosive and nearby explosive were Composition B and were modeled by JWL EOS as in the Pop plot calculation and the plexiglass gap was modeled by MG EOS. The simulated critical gap for the sympathetic detonation was well predicted as in the other published data. This implies that the code is valid for SDT simulation. In addition, it is a cost-effective simulation, since the code was developed on open-source code, so massive computation can then be run without license costs.